2017
DOI: 10.1080/10245332.2017.1375063
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome changes in leukemia: cytogenetics and molecular aspects

Abstract: The presence of these abnormalities can cause genetic instability in BM and result in the development of a malignant clone and progression of the disease. In addition, the evaluation of SCL together with the genes involved in these chromosomes can contribute to predict the disease prognosis as well as monitoring of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…present in approximately 6% of all male bone marrow karyotypes and in 16% of karyotypes from abnormal marrow 2,3 . The incidence of LOY in bone marrow cells increases proportionally with aging, with up to 20% of healthy men over 80 years of age showing LOY by conventional marrow karyotyping 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…present in approximately 6% of all male bone marrow karyotypes and in 16% of karyotypes from abnormal marrow 2,3 . The incidence of LOY in bone marrow cells increases proportionally with aging, with up to 20% of healthy men over 80 years of age showing LOY by conventional marrow karyotyping 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…LOY is observed in association with myeloproliferative neoplasms (MPN), myelodysplastic syndromes (MDS), acute myeloid leukemias (AML) and B-cell lymphomas/leukemias, often in the context of other chromosomal abnormalities 2,[6][7][8] . LOY is one of the most common recurrent cytogenetic abnormalities seen in MDS, with an incidence of up to 30% in males 3,5,[8][9][10][11][12][13] . The incidence of isolated LOY in MDS is lower, ranging from 4 to 10% 8,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The disease may be related to genetic, radiation, chemical substances, viral infection and other factors, which can lead to molecular alterations, such as gene mutation and chromosome rearrangements in the body ( 3 , 4 ). Accordingly, previous studies have revealed that the condition of leukemia may be associated with the high heterogeneity of cellular and molecular genetics; thus, chromosomal abnormalities and gene mutations are important prognostic indicators for patients with leukemia ( 5 , 6 ). In recent years, a number of studies have discovered that multiple long-chain non-coding RNAs (lncRNAs) are associated with the occurrence and development of leukemia, which may provide novel markers and targets for the diagnosis and therapy of leukemia ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…By aging, somatic mutations accumulate in the cells, which can be an initiator of cancer. When hematopoietic stem cells (HSCs) acquire certain mutations they can expand a clone of leukocytes in blood circulation (Ebert & Libby, 2018;Jaiswal et al, 2014;Shahrabi, Khodadi, Saba, Shahjahani, & Saki, 2018). This premalignant state is referred to as clonal hematopoiesis of indeterminate potential (CHIP).…”
Section: Introductionmentioning
confidence: 99%